A Linguistic Study of Village Names in Ngara District, Kagera Region, Tanzania - Elias, Tarasis Nahayo; Mpobela, Lea; Tibategeza, Eustard R. (International Journal of Culture and History, 2023)
This paper examines the linguistic features of village names in Ngara district in Kagera region -Tanzania.Itspecifically discusses the meanings, and the morphological and phonological features of Ngara village names. The natives speak two related Bantu languages, namely Kishubi and Kihangaza.The study focuses on village names since they are part of the historical, cultural and linguistic heritage of the given society. Additionally, place names have meaning as argued by several scholars (Anindo, 2016; Buberwa, 2012; Kihara, 2020; Wanjiru-mwita & Giraut, 2020) that nearly all African place names have meanings. Despite having meanings, place names differ in the way they are formed in each society hence, language specific. This uniqueness raised the need to investigate Ngara village names to see what they mean and how they are formed. This is a qualitative paper which employs two theories namely, Frame theory by Fillmore (1985) to define concepts that guided the retrieval of meanings of village namesand Lexeme-Morpheme Base Morphology theory pioneered by Beard (1995) which assisted on observation and identification of structural patterns of Ngara village names. The paper employed descriptive research design with the data collected from eight informants. The informants were involved in semi- structured interview, questionnaire and focus group discussions. The findings reveal that all village names in Ngara district have meanings derived from various phenomena such as geographical features, flora and fauna, social services or behaviours, calamities, agricultural activities, boundaries, economic activities and famous people. Furthermore, the findings reveal that the formation of Ngara village names involves both the morphological (affixation, compounding and reduplication) and phonological (deletion, hardening and devoicing) processes.